The Impact of Dextrin-Activated Expanded Perlite and Vermiculite Particles on the Performance of Thermal Insulating Rapeseed Oil-Based Polyurethane Foam Composites - Agnė Kairytė; Aliona Levina (Applied Sciences, 2025)
To enhance the performance of polyurethane foams, fillers are often incorporated into the matrix. However, the interaction between the filler and the polyurethane matrix is crucial for achieving the desired property improvements. Therefore, surface modification of the fillers plays a vital role in optimizing this interaction. The current study aims to activate the surface of expanded vermiculite and perlite with dextrin to incorporate additional functional groups on the surface of the fillers via the ball-milling process, thereby improving the reaction with a polymer matrix. Applied surface activation with dextrin resulted in the formation of dextrin-Si-O-Si-dextrin linkages in the fillers, allowing for a maximum improvement of 11% and 9% in water absorption, as well as slightly positive changes in the water contact angle of polyurethane foam with dextrin-activated perlite and vermiculite, respectively, compared to non-activated fillers. It also resulted in noticeable differences in the foaming times and viscosity of the premixes, affecting the structure of rigid polyurethane foam composites. Compared to non-activated perlite and vermiculite filler polyurethane foam composites, the dynamic viscosity of polyurethane foam composites with dextrin-activated perlite and vermiculite reduced maximally 16 and 21 times, respectively. At the same time, the closed cell content increased, resulting in lower thermal conductivity values up to a 7.5 wt.% filler concentration. In addition, a rise in mechanical performance was also achieved. Compressive strength increased by a maximum of 61% and 71%, while tensile strength increased by a maximum of 36% and 20% for polyurethane foam composites with dextrin-activated perlite and vermiculite, respectively.